2018
DOI: 10.1016/j.chb.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Twitter-derived measures of sentiment towards minorities (2015–2016) and associations with low birth weight and preterm birth in the United States

Abstract: Introduction: The objective of this study was to investigate the association between state-level publicly expressed sentiment towards racial and ethnic minorities and birth outcomes for mothers who gave birth in that state. Methods: We utilized Twitter’s Streaming Application Programming Interface (API) to collect 1,249,653 tweets containing at least one relevant keyword pertaining to a racial or ethnic minority group. State-level derived sentiment towards racial and ethnic minorities were merged with data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…These physiological relationships tied to social isolation feel particularly consequential in light of the racial differences identified in this study in the degree to which stigma was felt, and its impact on social support—with Black and Hispanic women in particular more likely to describe stronger stigma tied to reduction in support received. Given what we know about racial disparities in pregnancy and birth outcomes[e.g., [30, 31]], and their ties to chronic and acute stress [32, 33], it is possible that some aspect of this pathway may be mediated by or partially determined by experiences of stigma, and in turn, ties to social support [34]. Further research could explore how this stigma may relate to or be caused by racism, and particularly on how, on a societal level, fertility is valued differentially by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…These physiological relationships tied to social isolation feel particularly consequential in light of the racial differences identified in this study in the degree to which stigma was felt, and its impact on social support—with Black and Hispanic women in particular more likely to describe stronger stigma tied to reduction in support received. Given what we know about racial disparities in pregnancy and birth outcomes[e.g., [30, 31]], and their ties to chronic and acute stress [32, 33], it is possible that some aspect of this pathway may be mediated by or partially determined by experiences of stigma, and in turn, ties to social support [34]. Further research could explore how this stigma may relate to or be caused by racism, and particularly on how, on a societal level, fertility is valued differentially by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Below, we describe results from our quantitative analyses, based on the SGD algorithmic classification of the sentiment (positive vs. neutral/negative) of 1,249,653 tweets containing at least one of the relevant keywords pertaining to a racial or ethnic minority group. Descriptive details of these tweets have been previously described [37]. Briefly, approximately 620,000 tweets were about Blacks, 205,000 about Hispanics, 270,000 about Asians, and 60,000 about Middle Eastern groups.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Eichstaedt et al found greater use of anger, negative emotion, and disengagement words on Twitter predicted county-level heart disease mortality [38]. Notably, previous research found more negative area-level sentiment towards blacks and Middle Eastern groups was related to worse individual-level birth outcomes, and this was true for the full population and for racial minorities [37]. Thus, a hostile social climate related to race may have implications for health and well-being, but developing valid and inexpensive measures remains an important research challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The data is free, publicly available, and considered as an important source of information for researchers from different disciplines. Many previous studies collected information from ACS and leveraged with Twitter data to analyze sentiment of the people in the arena of public health [28], urban spaces [38], politics [39,40], disasters management [41], racial conflicts [30,42], and gender disparity [43]. Thus, linking Twitter data with Coronavirus data is a common practice among the researchers to evaluate the impacts of socioeconomic and demographic characteristics on the sentiments of the people towards a subject of interest.…”
Section: Us Census Data and Socioeconomic Analysismentioning
confidence: 99%